2020
DOI: 10.21203/rs.3.rs-16726/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Perioperative Hypoalbuminemia is a Risk Factor for Wound Complications Following Posterior Lumbar Interbody Fusion

Abstract: Background: Although serum albumin levels are increasingly used as an indicator of nutritional status in the clinic, the relationship between perioperative hypoalbuminemia and wound complications after posterior lumbar interbody fusion in the treatment of lumbar degenerative disease remains ambiguous. The aim of this study was to evaluate perioperative serum albumin in relation to postoperative wound complications after posterior lumbar interbody fusion in the treatment of single-segment lumbar degenerative di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Ogimi et al suggested that albumin < 3g/dL was associated with occurrence of seasonal human coronavirus lower respiratory tract infection [37]. Zhongyuan et al suggested that preoperative serum albumin < 3.5g/dL was signi cantly correlated with surgical site infection (SSI) and postoperative serum albumin < 3.0 g/dL was signi cantly correlated with surgical wound dehiscence in lumbar spine surgeries [12]. Danan et al suggested that preoperative albumin was a signi cant predictor of wound infection in surgeries for head and neck cancer [38].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ogimi et al suggested that albumin < 3g/dL was associated with occurrence of seasonal human coronavirus lower respiratory tract infection [37]. Zhongyuan et al suggested that preoperative serum albumin < 3.5g/dL was signi cantly correlated with surgical site infection (SSI) and postoperative serum albumin < 3.0 g/dL was signi cantly correlated with surgical wound dehiscence in lumbar spine surgeries [12]. Danan et al suggested that preoperative albumin was a signi cant predictor of wound infection in surgeries for head and neck cancer [38].…”
Section: Resultsmentioning
confidence: 99%
“…Serum albumin concentration was proposed to be an important changeable factor increasing the risk of the IFP, and a perioperative albumin supplementation was recommended [9][10][11][12][13]. However, these hypotheses remain controversial and lack proofs from randomized controlled trials (RCTs) [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have demonstrated albumin's role in the healing process and associated hypoalbuminemia with woundrelated complications. [6,8] He et al showed a significant…”
Section: Discussion Albumin's Role In Healing Processmentioning
confidence: 99%
“…correlation between lower albumin levels and delayed wound healing in 554 patients undergoing single-level posterior lumbar fusion surgery. [6] Others found low albumin levels contributed to higher risks of major complications in spine surgery. [9] No association between hypoalbuminemia and reoperations/unplanned readmission Interestingly, we found no significant association between hypoalbuminemia and reoperations or unplanned readmissions.…”
Section: Impact Of Dialysismentioning
confidence: 99%